Determination of Nurse-Nurse Collaboration in Medical Clinics During the COVID-19 Pandemic - Esra Çavuşoğlu; Meral Gün (Association of Nurse Managers, 2022)
Aim: The research was conducted to determine nurse-nurse collaboration in medical clinics during the COVID-19 pandemic. Method: The research is descriptive, and the sample consisted of 71 nurses working in the medical clinics of a university hospital. Data were collected using a personal information form and the Nurse-Nurse Collaboration Scale. While evaluating the data, numbers and percentages, minimum, maximum, and average values, t-test, and variance analysis were used. Results: In our research, the total mean score of the Nurse-Nurse Collaboration Scale was determined as 78.12+-12.26. Considering the number of items from the Nurse-Nurse Collaboration Scale sub-dimensions, the conflict management sub-dimension (4 items) mean score was the highest (13.26+-1.97), followed by the professionalism sub-dimension (8 items) (25.56+- 5.15), and the mean communication score was the lowest (11.52+-2.02). Conclusion: In our study, the level of nurse-nurse collaboration was determined to be high.